The Effect of the Use of Information Technology on Employee Work Efficiency - Fitra Nurhakim; Sri Lestari (Postgraduate, University of Mataram, 2023)
The millennial era is an era when technology in the information sector greatly supports performance with various functions and goals. The need for development in its use in agencies that utilize information technology must be reviewed from the work efficiency of employees and the impact of this work efficiency needs to be analyzed through structured measurements. Researchers formulate the problem of the impact of the use of Information Technology (IT) on employees to measure work efficiency in the company. The research method used is quantitative which will draw data from the field and be analyzed as a reference for the impact of Information Technology (IT) on employee work efficiency. The results of this study are the achievement of indicators of success or better levels of performance as evidenced by the indicators namely: individual competency, organizational support, and management support.